Trade and the environment fundamental issues in international law, WTO law, and legal theory - Vranes, Erich 1970- (Oxford University Press, 2009)
The relationship between WTO law and international and domestic efforts to protect the environment is a central concern in WTO and international environmental law. These issues are analysed here by examining the fundamental provisions of WTO law and exploring its interaction with general international law and national law
Includes bibliographical references and index
Keywords: World Trade Organization; Internationales Umweltrecht; Welthandel; Umweltrecht / (DE-627)091396107 / (DE-2867)15769-3; Internationales Recht / (DE-627)091368707 / (DE-2867)16186-1; WTO-Recht / (DE-627)091401860 / (DE-2867)19326-3; Internationales Wirtschaftsrecht / (DE-627)091368758 / (DE-2867)10621-4; Rechtswissenschaft / (DE-627)091385717 / (DE-2867)15976-5; International trade / Environmental aspects; Environmental law, International; Foreign trade regulation